ENHANCING STROKE PATIENT SATISFACTION THROUGH SERVICE QUALITY, TRUST, AND PATIENT-CENTERED CARE - Zaim Tsaqif Qisthi Haidi; Diyah Probowulan; Haris Hermawan (Jurnal Ilmiah Akuntansi, Manajemen dan Ekonomi Islam (JAM-EKIS), 2026)
Patient satisfaction is an essential indicator of healthcare performance, particularly in stroke care, which involves complex and long-term treatment. This study examines the effects of service quality and trust on stroke patient satisfaction, with Patient-Centered Care (PCC) as a mediating variable, at RSI PKU Muhammadiyah Pekajangan Pekalongan. Using a quantitative explanatory approach, data were collected from 150 stroke patients through structured questionnaires selected via proportional and purposive sampling. The data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS. The findings reveal that service quality has a significant positive effect on patient satisfaction and PCC. Trust significantly influences PCC but does not directly affect patient satisfaction. PCC has a significant positive effect on patient satisfaction and mediates the relationships between service quality and satisfaction as well as between trust and satisfaction. These results emphasize the importance of enhancing service quality and trust through patient-centered care implementation to improve stroke patient satisfaction and healthcare service outcomes.